Wavelet based fault analysis in HVDC system - Yeap, Yew Ming (2015)
HVDC system has become practically mature over the years but it is still met with some protection issues which should be discussed, for example, the circuit breaker (CB) should be selective to not trip if the transient is temporary, such as overcurrent due to load change. This paper addresses the problem with identifying the type of faults in a HVDC system using wavelet transform (WT). The wavelet transform is proven to be able to capture the distinctive feature of the fault pattern, specifically fault current rising time and oscillation pattern, which are helpful to form a basis for the tripping decision. Three phase-to-ground fault and DC fault are of concern in this paper as their effects are the most detrimental to the system. The point- to-point HVDC system is simulated using PSCAD, and the simulation result is subsequently processed in MATLAB to perform the wavelet transform.